Chronic perfluorooctanesulphonic acid (PFOS) exposure produces estrogenic effects in zebrafish. (November 2016) - Chen, Jiangfei; Wang, Xiaotong; Ge, Xiaoqing; Wang, Dingding; Wang, Ting; Zhang, Lingnan; Tanguay, Robert L.; Simonich, Michael; Huang, Changjiang; Dong, Qiaoxiang
Abstract: Perfluorooctanesulphonic acid (PFOS) is a ubiquitous contaminant in the aquatic environment and our earlier studies demonstrated that chronic PFOS exposures lead to a female-biased sex ratio and decreased sperm quality in male zebrafish. The underlying mechanism for these reproductive effects is unknown. In the present study, 8 h post-fertilization (hpf) zebrafish were exposed to PFOS at 250 μg/L for 5 months, and the levels of sex hormones, expression of sex determination related genes, and histological and ultrastructural changes of gonads were fully characterized. During the sex differentiation period, we observed elevated estradiol (E2) and decreased testosterone (T) levels in whole tissue homogenates from PFOS exposed juveniles. In fully mature adult male fish, serum E2 levels were slightly increased, however, the estrogen receptor alpha ( esr1 ) was significantly elevated in PFOS treated male gonads. Histological and electron microscopic examinations revealed structural changes in the gonads of PFOS exposed male and female adult zebrafish. In summary, chronic PFOS exposure disrupts sex hormone level and related gene expression and impairs gonadal development, which may contribute to the previously reported PFOS reproductive toxicity. Graphical abstract: Highlights: Chronic PFOS exposure produces a female-biased sex ratio in zebrafish. Chronic PFOS exposure reduces sperm quality in zebrafish. Chronic PFOS exposure increases estrogen level in juvenile and adult zebrafish. Chronic PFOS exposure alters expression of key genes involved hormone pathways. Chronic PFOS exposure alters male and femalegonadal structures in zebrafish.